Thermoplastic molding composition and molded article
By optimizing the combination of polyamide, polyphenylene ether, glass filler and metallic acid, the relative permittivity and mechanical properties of thermoplastic molded compounds are improved, and sufficient metallization is achieved after laser irradiation, thus solving the existing technology dielectric The problems of high loss factor and poor metallization are suitable for high-frequency electromagnetic wave communication applications.
Patent Information
- Application Number
- CN202110687834.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-22
- Filing Date
- 2021-06-21
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2041-06-21
AI Technical Summary
The glass fiber reinforced molding compounds of existing polyamide and polyphenylene ether substrates have problems such as high dielectric loss factor, insufficient mechanical properties and difficulty in processing in high-frequency electromagnetic wave communication applications, and have poor metallization after laser irradiation.
The thermoplastic molded compounds consisting of polyamide, polyphenylene ether, glass filler, titanate, stannate, zirconate and their mixtures, and LDS additives are used to improve their relative capacitance by optimizing component ratio and structural design. , dielectric loss factor and mechanical properties, and sufficient metallization is achieved after laser irradiation.
The relative capacity is at least 5.0, the dielectric loss factor is less than 0.008, good mechanical properties and sufficient metallization after laser irradiation, and is suitable for the housing and components of high-frequency electromagnetic wave communication devices.
Smart Images

Figure GDA0005150316850000271 
Figure GDA0005150316850000281 
Figure GDA0005150316850000282
Abstract
Description
Technical Field
[0001] The present invention relates to glass fiber reinforced thermoplastic molding compounds based on polyamide and polyphenylene ether with high relative permittivity and low dielectric loss factor, as well as moldings made from these molding compounds and their use. The molding compounds also contain LDS additives, and the moldings made from these molding compounds can be selectively metallized after local irradiation. Background Art
[0002] Plastic molding compounds having high relative permittivity and low dielectric loss factor are advantageously used for manufacturing housings, housing parts or other components of devices that communicate via electromagnetic waves with a frequency of 0.3 GHz to 300 GHz, because their use avoids significant impairment of the transmission and reception performance of these devices.
[0003] Devices communicating via such electromagnetic waves are used in many areas, for example in telecommunications, consumer electronics or household goods, in particular transmitting and receiving devices, mobile phones, tablets, laptops, navigation devices, surveillance cameras, cameras, sensors, diving computers, audio systems, remote controls, loudspeakers, headphones, radios, televisions, kitchen appliances, door opening devices or door openers, control units for vehicle central locking systems, vehicle keys for keyless start, temperature measuring and display devices, measuring devices and control units.
[0004] The polyamide molding compounds described in EP 3 330 319 A1 have a relative permittivity of not more than 3.5 at a frequency of 2.45 GHz. In addition to a special mixture of aliphatic polyamide and amorphous polyamide or microcrystalline polyamide, the molding compound also contains a glass filler and an additive, the glass filler consisting of glass with a content of alkali metal oxides and alkaline earth metal oxides of 0% to 12% by weight. Regardless of the composition, the relative permittivity of all working examples and comparative examples is less than 4.0. No information is provided on the dielectric loss factor and metallization.
[0005] EP 3 560 987 A1 describes a glass fiber reinforced molding compound with high tensile strength and high impact strength and low dielectric constant and low dielectric loss factor. The molding compound comprises 10% to 90% by weight of glass fibers and 90% to 10% by weight of plastics, and the glass fiber composition is described in more detail. Compared with E-glass, the above-mentioned glass fibers comprise significantly less alkaline earth metal oxides, but comprise a higher content of boron oxide, reduce the dielectric constant to 4.8, and reduce the dielectric loss factor to 0.0015 (all measured at 10GHz). As shown in the disclosed embodiments, improved dielectric properties can also be applied to polyamide molding compounds. However, for the molding compound of PA6 and 50% by weight of glass fibers, a relative permittivity less than 4.0 and a dielectric loss factor of at least 0.0109 were determined. Information on the metallization of the molding compound is not provided.
[0006] EP 2 291 444 describes laser direct structurable (LDS) molding compounds having a high dielectric constant of at least 4 and a low dielectric loss factor of at most 0.01. The molding compounds comprise a base resin, an LDS additive and a ceramic filler having a dielectric constant of ≥ 25. In the examples, the Dk of the molding compounds based on polyamide and polyphenylene ether is shown to be in the range of 4.1 to 6.8. However, the dielectric loss factor of the molding compounds described in the examples is not disclosed. Summary of the invention
[0007] Based on the above, one task of the present invention is to provide a thermoplastic molding compound which, in addition to a relative permittivity of at least 5.0 and a low dielectric loss factor of less than 0.008, can also be easily processed by injection molding and has in particular good injection shrinkage and warpage / deformation behavior. In addition, the thermoplastic molding compound should have good mechanical properties, preferably the molding compound should have a fracture stress of at least 70 MPa and a tensile modulus of at least 5000 MPa. In addition, the molding compound should have good metallization after laser irradiation.
[0008] This object is achieved by a thermoplastic molding compound according to the invention, which consists of the following components:
[0009] (A) a mixture of at least one polyamide (A1), at least one polyphenylene ether (A2) and optionally a compatibilizer (A3) and optionally an olefin and / or vinyl aromatic polymer (A4);
[0010] (B) 10 to 40 weight percent of a glass filler having a glass composition comprising at least 10.0 weight percent boron oxide and at most 15 weight percent of magnesium oxide and calcium oxide combined;
[0011] (C) 20 to 50 weight percent of titanates, stannates, zirconates, and mixtures thereof;
[0012] (D) 1 wt % to 8 wt % of an LDS additive;
[0013] (E) 0 to 5 wt% of additives other than components (A), (B), (C) and (D);
[0014] wherein the mixture (A) consists of 80 to 100% by weight of a mixture (M) of components (A1), (A2) and (A3) and 0 to 20% by weight of component (A4), based in each case on the sum of components (M) and (A4), and wherein the sum of components (M) and (A4) is 100% by weight of the mixture (A);
[0015] and wherein the mixture (M) consists of 36 to 92% by weight of component (A2), 8 to 60% by weight of component (A1) and 0 to 4% by weight of component (A3), in each case based on the sum of components (A1) to (A3), and wherein the sum of components (A1) to (A3) is 100% by weight of the mixture (M);
[0016] and wherein the sum of (B) and (C) is 35 wt % to 70 wt % based on the sum of components (A) to (E);
[0017] And wherein the sum of components (A) to (E) is 100% by weight of the molding composition.
[0018] As for the composition of the mixture (A), it can be seen from the above that the components (A1), (A2) and (A3) together account for 80% to 100% by weight of the mixture (A), and the content of the component (A4) in the mixture (A) is 0% to 20% by weight. The mixture of components (A1), (A2) and (A3) is referred to as component (M). In addition to components (A1) to (A4), the mixture (A) does not contain any other components.
[0019] The thermoplastic molding composition according to the present invention and the molded article made of the thermoplastic molding composition have a relative permittivity of at least 5.0 and a dielectric loss factor (DLF) of less than 0.008. Herein, the relative permittivity and DLF are measured according to IEC 61189-2-721 (2015) on a flat plate of 80 mm × 80 mm × 3 mm using a split postdielectric resonator (SPDR) of QWED, Poland, at a measuring frequency of 2.45 GHz and a temperature of 23 ° C.
[0020] By good mechanical properties, it is understood that the molding compound according to the invention has a tensile modulus of at least 5000 MPa, preferably at least 6000 MPa and / or a stress at break of at least 70 MPa, preferably at least 75 MPa and / or an elongation at break of at least 0.8%, preferably at least 0.9%. In this context, the tensile modulus, stress at break and elongation at break are determined according to ISO 527 (2012).
[0021] Good metallization in the sense of the present invention means that a molding (flat 60 mm×60 mm×2 mm) injection-molded from the thermoplastic molding compound of the invention can be fully metallized in a copper plating bath after partial irradiation with an Nd:YAG laser (FOBADP50 laser, wavelength=1064 nm, irradiation width=50 μm, speed=4 m / s). For this purpose, during the laser structuring process, 16 adjacent 10 mm×10 mm areas were irradiated on the surface of the molded part, whereby both the pulse frequency of the laser (5 kHz, 6 kHz, 7 kHz and 8 kHz) and the current intensity (24 amperes to 25.5 amperes) were varied. The cleaned molding was then metallized in a reducing copper plating bath (MacDermid MID-Copper 100B1) for 20 to 30 minutes. In this context, full metallization means that copper is deposited in at least 14 areas with an average thickness of at least 3 μm. DETAILED DESCRIPTION
[0022] Surprisingly, it has been found that the abovementioned object is achieved by a thermoplastic molding composition which consists of:
[0023] (A) a mixture of at least one polyamide (A1), at least one polyphenylene ether (A2) and optionally a compatibilizer (A3) and optionally an olefin and / or vinyl aromatic polymer (A4);
[0024] (B) 10 to 40 weight percent of a glass filler having a glass composition comprising at least 10.0 weight percent boron oxide and at most 15 weight percent of magnesium oxide and calcium oxide combined;
[0025] (C) 20 to 50 weight percent of titanates, stannates, zirconates, and mixtures thereof;
[0026] (D) 1 wt % to 8 wt % of an LDS additive;
[0027] (E) 0 to 5 wt% of additives other than components (A), (B), (C) and (D);
[0028] wherein the mixture (A) consists of 80% to 100% by weight of a mixture (M) of components (A1), (A2) and (A3) and 0% to 20% by weight of a component (A4); in each case based on the sum of components (M) and (A4), and wherein the sum of components (M) and (A4) is 100% by weight of the mixture (A)
[0029] and wherein the mixture (M) consists of 36 to 92% by weight of component (A2), 8 to 60% by weight of component (A1) and 0 to 4% by weight of component (A3), in each case based on the sum of components (A1) to (A3), and wherein the sum of components (A1) to (A3) is 100% by weight of the mixture (M);
[0030] and wherein the sum of (B) and (C) is 35 wt % to 70 wt % based on the sum of components (A) to (E);
[0031] And wherein the sum of components (A) to (E) is 100% by weight of the molding composition.
[0032] The content of mixture (A) in the molding composition is the difference between the sum of the contents of (B) to (E) and 100% by weight of the total molding composition.
[0033] Component (A) of the molding compound is preferably present in a proportion of 24 to 57.9% by weight, particularly preferably in a proportion of 31 to 51.8% by weight, based on the total weight of the molding compound (sum of components (A) to (E)).
[0034] The proportion of component (B) is preferably in the range from 15% to 35% by weight, particularly preferably in the range from 18% to 32% by weight, based in each case on the sum of (A) to (E).
[0035] The proportion of component (C), based in each case on the sum of (A) to (E), is preferably 25% to 45% by weight, particularly preferably 30% to 42% by weight.
[0036] The proportion of the sum of components (B) and (C) is preferably 40% to 65% by weight, and particularly preferably 45% to 60% by weight, based on the sum of (A) to (E).
[0037] The proportion of component (D) is preferably 2% to 6% by weight, particularly preferably 3% to 5% by weight, based in each case on the sum of (A) to (E).
[0038] The proportion of component (E) is preferably 0.1% to 5% by weight, particularly preferably 0.2% to 4% by weight, based in each case on the sum of (A) to (E).
[0039] As studies have shown, glass-fiber reinforced molding compounds whose polymer matrix consists exclusively of polyamide have too high a dielectric loss factor, even when so-called "low-DK glass fibers" are used as reinforcing fibers. In contrast, molding compounds with a matrix of polyphenylene ether exhibit too high warpage and, in particular, too high shrinkage values and can only be processed poorly. Molding compounds with a polymer component formed from a 1:1 mixture of polyamide and polyphenylene ether and which are reinforced with glass fibers consisting of E-glass also exhibit excessive dielectric losses.
[0040] Definition of terms
[0041] For the purposes of the present invention, the term "polyamide" (abbreviation PA) is understood as a generic term comprising homopolyamides and copolyamides. The selected spellings and abbreviations of polyamides and their monomers correspond to those specified in ISO standard 16396-1 (2015, (D)). The abbreviations used herein are used synonymously with the IUPAC names of the monomers hereinafter; specifically, the following abbreviations of the monomers appear: T or TPS for terephthalic acid, I or IPS for isophthalic acid, MACM for bis(4-amino-3-methylcyclohexyl)methane (also known as 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane, CAS No. 6864-37-5), PACM for bis(4-aminocyclohexyl)methane (also known as 4,4'-diaminodicyclohexylmethane, CAS No. 1761-71-3), TMDC for bis(4-amino-3,5-dimethylcyclohexyl)methane (also known as 3,3',5,5'-tetramethyl-4,4'-diaminodicyclohexylmethane, CAS No. 65962-45-0). For 1,6-hexanediamine (also known as hexamethylenediamine), the abbreviation HMDA is used.
[0042] Compared to semicrystalline polyamides, amorphous polyamides exhibit no or only very low, hardly detectable heat of fusion. In dynamic differential scanning calorimetry (DSC) according to ISO 11357-2 (2013), amorphous polyamides exhibit a heat of fusion of preferably less than 5 J / g, particularly preferably not more than 3 J / g, very particularly preferably 0 J / g to 1 J / g at a heating rate of 20 K / min. Due to the amorphous nature of amorphous polyamides, they do not have a melting point.
[0043] In addition to the glass transition temperature, microcrystalline polyamides also have a melting point. However, they have a morphology in which the crystallites have such a small size that a sheet made therefrom with a thickness of 2 mm is still transparent, i.e. its light transmittance measured in accordance with ASTM D1003-13 (2013) is at least 90% and its haze is at most 3%. In dynamic differential scanning calorimetry (DSC) in accordance with ISO 11357-2 (2013), microcrystalline polyamides exhibit a heat of fusion of preferably 5 J / g to 25 J / g, particularly preferably 5 J / g to 22 J / g, very particularly preferably 5 J / g to 20 J / g at a heating rate of 20 K / min.
[0044] In addition to the glass transition temperature, the semi-crystalline polyamide has a distinct melting point and, in dynamic differential scanning calorimetry (DSC) according to ISO 11357-2 (2013), exhibits a heat of fusion of preferably more than 25 J / g, particularly preferably more than 30 J / g, most preferably from 30 J / g to 80 J / g at a heating rate of 20 K / min.
[0045] Relative permittivity and dielectric loss factor
[0046] Permittivity (ε) is an indicator of the behavior of a molecule when it is introduced into an electric field. It is expressed by the equation ε = ε r ·ε0 and relative permittivity (ε r ) is related to the permittivity of the vacuum (ε0). r ) depends on the amount of substance and is the quotient of the permittivity (ε) and the vacuum permittivity (ε0). In addition to the type of substance, the relative permittivity (ε r ) also depends on the frequency of the electric field and the temperature.
[0047] The dielectric loss factor indicates how much loss there is in the propagation of electromagnetic waves in an electrical component such as a capacitor or in a substance such as a plastic molding compound. Losses here refer to energy that is converted electrically or electromagnetically and dissipated as heat, for example. These losses attenuate the electromagnetic waves. To express the loss factor more precisely, consider a capacitor connected to a voltage source that has a sinusoidal voltage curve over time. A phase shift occurs between voltage and current in such a capacitor. The phase shift of an ideal lossless capacitor is For a true lossy capacitor, the phase shift is less than the 90° loss angle δ and the dielectric loss factor is equal to tan δ. The dielectric loss factor is therefore a measure of the amount of energy absorbed by an insulating material in an alternating field and converted into lost heat. Materials with a high loss factor are not suitable for use as insulating or housing materials for high-frequency applications. The relative permittivity and dielectric loss factor are preferably determined according to IEC 61189-2-721 (2015).
[0048] Component (A)
[0049] The thermoplastic molding composition according to the invention comprises as polymer component a mixture (A) of at least one polyamide (A1), at least one polyphenylene ether (A2) and optionally a compatibilizer (A3) and optionally an olefin and / or vinylaromatic compound (A4).
[0050] In this case, the mixture (A) consists of 80 to 100% by weight of a mixture (M) of the components (A1), (A2) and (A3) and 0 to 20% by weight of a component (A4), the sum of the components (M) and (A4) being 100% by weight of the mixture (A) in each case, based on the sum of the components (M) and (A4).
[0051] The mixture (M) consists of 36% to 92% by weight of component (A2), 8% to 60% by weight of component (A1), 0% to 4% by weight of component (A3), in each case based on the sum of components (A1) to (A3).
[0052] Preferably, component (A1) is present in the mixture (M) in a proportion of 10% to 48% by weight, particularly preferably 10% to 45% by weight, based on the sum of (A1) to (A3).
[0053] Preferably, component (A2) is present in the mixture (M) in a proportion of 48% to 89.9% by weight, particularly preferably 52% to 89.8% by weight, based on the sum of (A1) to (A3).
[0054] Preferably, component (A3) is present in the mixture (M) in a proportion of 0.1% to 4% by weight, particularly preferably 0.2% to 3% by weight, based on the sum of (A1) to (A3).
[0055] Preferably, component (A4) is present in the mixture (A) in a proportion of 0% to 20% by weight, based on the sum of (M) and (A4), and particularly preferably, the mixture (A) does not contain component (A4). That is, the mixture (A) particularly preferably consists only of components (A1) to (A3).
[0056] Component (A1)
[0057] One embodiment of the present invention provides preferred aliphatic polyamides as component (A1). In particular, the aliphatic polyamides are preferably selected from the group consisting of PA46, PA6, PA66, PA 6 / 66, PA10, PA11, PA12, PA516, PA610, PA612, PA614, PA616, PA618, PA1010, PA1012, PA1014, PA 1016, PA1018, PA1212 and mixtures thereof. Aliphatic polyamides having an N / C ratio (N=nitrogen / C=carbon) greater than or equal to 8 are particularly preferred because they have a lower water absorption and therefore the dielectric properties change less in a humid environment. In particular, the aliphatic polyamides PA610, PA612, PA1010, PA12 and PA616 are preferred.
[0058] According to another embodiment of the invention, amorphous or microcrystalline polyamides are preferred as component (A1). In particular, the amorphous or microcrystalline polyamide is preferably selected from the group consisting of PA6I / 6T, PA MACM9, PAMACM10, PAMACM12, PAMACM13, PAMACM14, PA MACM16, PAMACM17, PAMACM18, PAPACM10, PAPACM12, PA PACM13, PAPACM14, PAPACM16, PAPACM17, PAPACM18, PA TMDC10, PATMDC12, PATMDC13, PATMDC14, PATMDC16, PA TMDC17, PATMDC18, PAMACM10 / 10, PAMACMI / 12, PAMACMT / 12, PA6I / MACMI / MACMT, PAMACMI / MACMT / MACM12, PAMACMI / MACMT / MACM12 / 12, PA / MACM12, PA 6I / 6T / MACMI, PAMACMI / MACM36, PA MACMT / MACM36, PAMACMI / MACM12, PA MACMT / MACM12, PA MACM6 / 11, PAMACM10 / 10, PAMACM12 / PACM12, PA MACM14 / PACM14, PA MACM18 / PACM18 and mixtures thereof, among which PA 6I / 6T, PA MACM12, PAMACM14, PATMDC12, PA TMDC14, PA MACMI / 12, PA 6I / 6T / MACMI / MACMT, PAMACMI / MACMT / 12, PA MACMI / MACMT / MACM12, PA6I / 6T / MACMI / MACMT / 12, PA MACM10 / 10, PA MACM12 / PACM12, PAMACM14 / PACM14, PA MACM18 / PACM18 and mixtures thereof. Most preferred are PA 6I / 6T, PA MACM12, PA MACMI / 12, PA MACMI / MACMT / 12, PA MACMI / MACMT / MACM12, PA MACM12 / PACM12 and mixtures thereof.
[0059] According to another preferred embodiment, a semicrystalline partially aromatic polyamide is preferred as component (A1). The glass transition temperature of the semicrystalline partially aromatic polyamide is preferably from 90°C to 150°C, preferably from 110°C to 140°C, in particular from 115°C to 135°C. The melting point of the semicrystalline partially aromatic polyamide is from 255°C to 330°C, preferably from 270°C to 325°C, in particular from 280°C to 320°C. Preferably, the semicrystalline partially aromatic polyamide of component (A1) has a melting enthalpy of 25 J / g to 80 J / g, preferably from 30 J / g to 70 J / g, as determined by DSC according to ISO 11357 (2013).
[0060] The preferred semi-aromatic semi-crystalline polyamides herein are made of the following materials:
[0061] (a): dicarboxylic acids: 30 to 100 mol %, in particular 50 to 100 mol %, of terephthalic acid and 0 to 70 mol %, in particular 0 to 50 mol %, of at least one aliphatic dicarboxylic acid having 6 to 16 carbon atoms and / or 0 to 70 mol %, in particular 0 to 50 mol %, of at least one cycloaliphatic dicarboxylic acid having 8 to 20 carbon atoms and / or 0 to 50 mol % of isophthalic acid, in each case based on the total amount of dicarboxylic acids,
[0062] (b): diamines: based on the total amount of diamines, 80 mol % to 100 mol % of at least one aliphatic diamine having 4 to 18 carbon atoms, preferably having 6 to 12 carbon atoms, and 0 mol % to 20 mol % of at least one cycloaliphatic diamine, preferably having 6 to 20 carbon atoms, such as PACM, MACM, IPDA and / or 0 mol % to 20 mol % of at least one aromatic aliphatic diamine, such as MXDA and PXDA, and optionally
[0063] (c): Aminocarboxylic acid and / or lactam: each having 6 to 12 carbon atoms.
[0064] According to a preferred embodiment, the semicrystalline partially aromatic polyamide of component (A1) is based on at least 55 mol %, in particular at least 65 mol %, of terephthalic acid and at least 80 mol %, preferably at least 90 mol %, in particular at least 95 mol % of aliphatic diamines having 4 to 18 carbon atoms, preferably having 6 to 12 carbon atoms, and if desired further based on aliphatic, cycloaliphatic and aromatic dicarboxylic acids and lactams and / or aminocarboxylic acids.
[0065] According to another preferred embodiment, the aliphatic dicarboxylic acid (which can be used in addition to terephthalic acid) of the partially aromatic polyamide, for example component (A1), is selected from the group consisting of adipic acid, succinic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, brassic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, octadecanedioic acid and dimer fatty acids (36 C atoms). Adipic acid, sebacic acid and dodecanedioic acid are particularly preferred. Therefore, in addition to terephthalic acid, preferably used dicarboxylic acids are isophthalic acid, adipic acid, sebacic acid and dodecanedioic acid or mixtures of these dicarboxylic acids. In particular, polyamides (A1) based solely on terephthalic acid as dicarboxylic acid are preferred.
[0066] According to another preferred embodiment, the aliphatic diamine of the partially aromatic polyamide of component (A1) is selected from the group consisting of 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, methyl-1,8-octanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine or a mixture of these diamines, wherein 1,6-hexanediamine, 1,10-decanediamine, 1,12-dodecanediamine or a mixture of these diamines is preferred, and wherein 1,6-hexanediamine and 1,10-decanediamine are particularly preferred. In addition to the aliphatic diamines, cycloaliphatic and / or aromatic aliphatic diamines may be substituted in a concentration of 0 mol % to 20 mol %, based on the total amount of diamines.
[0067] Further preferably, the polyamide (A1) is formed from the following components:
[0068] (a): dicarboxylic acids: in each case, based on the total content of dicarboxylic acids present, 50 to 100 mol % of terephthalic acid, 0 to 50 mol % of aliphatic dicarboxylic acids preferably having 6 to 12 carbon atoms, and / or cycloaliphatic dicarboxylic acids preferably having 8 to 20 carbon atoms and / or isophthalic acid;
[0069] (b): Diamines: Based on the total content of diamines present, 80 mol % to 100 mol % of at least one aliphatic diamine having 4 to 18 carbon atoms, preferably 6 to 12 carbon atoms; 0 mol % to 20 mol % of cycloaliphatic diamines, for example, preferably having 6 to 20 carbon atoms. For example PACM, MACM, IPDA and / or aromatic aliphatic diamines, such as MXDA and PXDA, wherein the mole percentage content of dicarboxylic acid in the refractory polyamide is 100%, the mole percentage content of diamine is 100%, and optionally from:
[0070] (c): aminocarboxylic acids and / or lactams comprising lactams preferably having 6 to 12 carbon atoms and / or aminocarboxylic acids preferably having 6 to 12 carbon atoms.
[0071] Although components (a) and (b) are preferably used in equimolar amounts, the concentration of (c) is preferably up to 30% by weight, preferably up to 20% by weight, particularly preferably up to 15% by weight, based in each case on the sum of (a) to (c).
[0072] Suitable cycloaliphatic dicarboxylic acids are cis- and / or trans-cyclohexane-1,4-dicarboxylic acid and / or cis- and / or trans-cyclohexane-1,3-dicarboxylic acid (CHDA). The above-mentioned aliphatic diamines commonly used may be substituted by other diamines in a subordinate amount of not more than 20 mol %, preferably not more than 15 mol %, in particular not more than 10 mol %, based on the total amount of diamines. As cycloaliphatic diamines, for example, cyclohexanediamine, 1,3-bis-(aminomethyl)-cyclohexane (BAC), isophoronediamine (IPDA), norbornanedimethylamine, 4,4'-diaminodicyclohexylmethane (PACM), 2,2-(4,4'-diaminodicyclohexyl)propane (PACP) and 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane (MACM) can be used. As aromatic aliphatic diamines, meta-phenylenediamine (MXDA) and para-phenylenediamine (PXDA) should be mentioned.
[0073] In addition to the dicarboxylic acids and diamines described, lactams and / or aminocarboxylic acids can also be used as components for forming polyamides (component (c)). Suitable compounds are, for example, caprolactam (CL), α,ω-aminocaproic acid, α,ω-aminononanoic acid, α,ω-aminoundecanoic acid (AUA), laurolactam (LL) and α,ω-aminododecanoic acid (ADA). The concentration of aminocarboxylic acids and / or lactams used together with components (A1-a) and (A1-b) is up to 20% by weight, preferably up to 15% by weight, particularly preferably up to 12% by weight, based on the sum of components (A1a) to (A1c). Lactams or α,ω-amino acids having 4, 6, 7, 8, 11 or 12 C atoms are particularly preferred. These are respectively the lactam pyrrolidin-2-one (4 C atoms), ε-caprolactam (6 C atoms), enantholactam (7 C atoms), octanoic acid lactam (8 C atoms), laurolactam (12 C atoms), α,ω-amino acids 1,4-aminobutyric acid, 1,6-aminocaproic acid, 1,7-aminoheptanoic acid, 1,8-aminooctanoic acid, 1,11-aminoundecanoic acid and 1,12-aminododecanoic acid. In a particularly preferred embodiment, component (A1) does not contain caprolactam or aminocaproic acid or does not contain any aminocarboxylic acids or lactams.
[0074] Regulators in the form of monocarboxylic acids or monoamines can be added to the batch and / or the precondensate (before postcondensation) to control the molecular weight, relative viscosity, flowability or MVR. Suitable aliphatic, cycloaliphatic or aromatic monocarboxylic acids or monoamines as regulators are acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, lauric acid, stearic acid, 2-ethylhexanoic acid, cyclohexanoic acid, benzoic acid, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, 3,5-di-tert-butyl-4-hydroxybenzoic acid, 3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionic acid, 2-(3,5-di-tert-butyl-4-hydroxybenzylthio)acetic acid, 3,3 -bis(3-tert-butyl-4-hydroxyphenyl)butyric acid, butylamine, pentylamine, hexylamine, 2-ethylhexylamine, n-octylamine, n-dodecylamine, n-tetradecylamine, n-hexadecylamine, stearylamine, cyclohexylamine, 3-(cyclohexylamino)-propylamine, methylcyclohexylamine, dimethylcyclohexylamine, benzylamine, 2-phenylethylamine, 2,2,6,6-tetramethylpiperidin-4-amine, 1,2,2,6,6-pentamethylpiperidin-4-amine, 4-amino-2,6-di-tert-butylphenol, etc. The regulator can be used alone or in combination. Other monofunctional compounds that can react with amino or acid groups, such as anhydrides, isocyanates, acyl halides or esters, can also be used as regulators. The usual amount of the regulator is 10 to 200 mmol per kilogram of polymer.
[0075] Specific representatives of the semi-crystalline partially aromatic polyamide (A1) are: PA 4T / 4I, PA4T / 6I, PA 5T / 5I, PA6T / 6, PA 6T / 6I, PA6T / 6I / 6, PA6T / 66, 6T / 610, 6T / 612, PA6T / 10T, PA6T / 10I, PA9T, PA10T, PA12T, PA10T / 10I, PA10T / 106, PA10T / 610, PA10T / 612, PA10T / 66, PA10T / 6, PA10T / 1010, PA10T / 1012, PA 10T / 12, PA10T / 11, PA6T / 9T, PA6T / 12T, PA6T / 10T / 6I, PA 6T / 6I / 6, PA6T / 6I / 12 and mixtures thereof, particularly preferably, the partially aromatic polyamide of component (A1) is selected from the group consisting of PA6T / 6I, PA6T / 10T, PA6T / 10T / 6I and mixtures thereof. Preferred are polyamides (A1) containing 6T units, in particular at least 10% by weight of 6T units.
[0076] Therefore, according to the present invention, the following partially aromatic copolyamides are particularly preferred as polyamide (A1):
[0077] semicrystalline polyamide 6T / 6I having 55 to 75 mol % of hexamethylene terephthalamide units and 25 to 45 mol % of hexamethylene isophthalamide units;
[0078] semicrystalline polyamide 6T / 6I having 62 to 73 mol % of hexamethylene terephthalamide units and 25 to 38 mol % of hexamethylene isophthalamide units;
[0079] Semicrystalline polyamides prepared from a mixture of at least 50 mol % of terephthalic acid and up to 50 mol % of isophthalic acid, in particular 100 mol % of terephthalic acid and at least two diamines selected from the group consisting of hexamethylenediamine, nonamethylenediamine, methyloctanediamine and decanediamine;
[0080] Semicrystalline polyamides prepared from a mixture of 70 mol % to 100 mol % terephthalic acid and 0 mol % to 30 mol % isophthalic acid and hexamethylenediamine and dodecanediamine;
[0081] A semicrystalline polyamide prepared from a mixture of at least 50 mol % of terephthalic acid and not more than 50 mol % of dodecanedioic acid with at least two diamines selected from the group consisting of hexamethylenediamine, nonanediamine, methyloctanediamine and decanediamine;
[0082] semicrystalline polyamide 6T / 10T having 10 to 60 mol %, preferably 10 to 40 mol %, of hexamethyleneterephthalamide (6T) units and 40 to 90 mol %, preferably 60 to 90 mol %, of decamethyleneterephthalamide (10T) units;
[0083] Semicrystalline polyamide 6T / 10T / 6I having 50 to 90 mol %, preferably 50 to 70 mol %, of hexamethylene terephthalamide (6T) units and 5 to 45 mol %, preferably 10 to 30 mol % of hexamethylene isophthalamide (6I) units and 5 to 45 mol %, preferably 20 to 40 mol % of decamethylene terephthalamide (10T) units;
[0084] Solution viscosity η of polyamide (A1) rel Determined in accordance with ISO 307 (2007) on a solution of 0.5 g of the polymer in 100 ml of m-cresol at 20° C., preferably 1.3 to 2.7, particularly preferably 1.4 to 2.3 and particularly preferably 1.5 to 2.0.
[0085] Component (A2)
[0086] The polyphenylene ethers used according to the invention are known. They are prepared by conventional methods from phenols disubstituted in the ortho position by alkyl groups by oxidative coupling (see U.S. Pat. Nos. 3,661,848, 3,378,505, 3,306,874, 3,306,875 and 3,639,656). Catalysts based on heavy metals such as copper, manganese or cobalt in combination with other substances (e.g. secondary amines, tertiary amines, halogens or combinations thereof) are usually used for the preparation.
[0087] Suitable polyphenylene ethers include poly(2,6-dimethyl-1,4-phenylene) ether, poly(2,6-diethyl-1,4-phenylene) ether, poly(2-methyl-6-ethyl-1,4-phenylene) ether, poly(2-methyl-6-propyl-1,4-phenylene) ether, poly(2,6-dipropyl-1,4-phenylene) ether, poly(2-ethyl-6-propyl-1,4-phenylene) ether or copolymers, for example copolymers containing 2,3,6-trimethylphenol and mixtures thereof. Preferred is poly(2,6-dimethyl-1,4-phenylene) ether optionally in combination with 2,3,6-trimethylphenol units. The polyphenylene ether can be used in the form of a homopolymer, a copolymer, a graft copolymer, a block copolymer or an ionomer.
[0088] Suitable polyphenylene ethers have an intrinsic viscosity of preferably 0.1 dl / g to 0.6 dl / g measured in chloroform at 25°C. This corresponds to a molecular weight Mn (number average) of 3,000 to 40,000 grams per mole and a weight average molecular weight Mw of 5,000 to 80,000 grams per mole. Combinations of high and low viscosity polyphenylene ethers can be used. The ratio of the two polyphenylene ethers of different viscosities depends on the viscosity and the desired physical properties.
[0089] In order to improve the compatibility between component (A1) and component (A2), in a preferred embodiment, the polyphenylene ethers used are modified so that they preferably contain carbonyl, carboxyl, carboxylic acid, anhydride, amide, imide, carboxylate, carboxylate, amino, hydroxyl, epoxy, oxazoline, carbamate, urea, lactam or covalently bonded halogenated benzyl groups. Preferably, for this purpose, the unmodified polyphenylene ether (A2) is modified with α,β-unsaturated dicarbonyl compounds having polymerizable double bonds, monomers containing amide groups or lactam groups (A3), optionally in combination with free radical starters (A3), for example peroxides, in particular dibenzoyl peroxide, as described, for example, in EP 0 654 505 A1.
[0090] Component (A3)
[0091] To improve the compatibility of components (A1) and (A2), compatibilizers can be used in the form of functional compounds that interact with the polyphenylene ether, the polyamide or both. The interaction can be chemical (e.g. by grafting) and / or physical (e.g. by influencing the surface properties of the dispersed phase).
[0092] In a preferred embodiment of the present invention, the compatibilizer further comprises a free radical initiator, which is preferably an organic peroxide or an azo compound. That is, in this embodiment, the compatibilizer is graft polymerized in the presence of a free radical initiator.
[0093] In a particularly preferred embodiment, the compatibilizer is used in the absence of a free radical initiator.
[0094] The compatibilizer may be a functional compound containing at least one carboxylic acid, carboxylic anhydride, epoxy, ester, amide or imide group, preferably double bonded to an olefin. Examples include maleic acid, maleic anhydride, fumaric acid, acrylic acid, methacrylic acid, methyl maleic acid, methyl maleic anhydride, itaconic acid, itaconic anhydride, butenyl succinic acid, butenyl succinic anhydride, tetrahydrophthalic acid, tetrahydrophthalic anhydride, N-phenyl maleimide, citric acid, malic acid and 2-hydroxy nonadecane-1,2,3-tricarboxylic acid, monoesters or diesters of the above acids with C1- to C12-alcohols such as methanol or ethanol, monoamides or diamides of the above acids which may be substituted on nitrogen by alkyl or aryl groups having up to 12 carbon atoms, and salts of alkali metals or alkaline earth metals such as calcium and potassium. Particularly preferred are maleic acid, fumaric acid, maleic anhydride and citric acid. The compatibilizer can be added directly during the preparation of the blend, either alone or in combination with an optional free radical initiator, or the polyphenylene ether and / or polyamide can be functionalized with the compatibilizer in a separate step.
[0095] Suitable free radical initiators are, for example: 1,1-di-tert-butyl-peroxy-3,3,5-trimethylcyclohexane, tert-butyl-peroxyisopropyl carbonate, tert-butyl-peroxy-3,3,5-trimethylhexanoate, tert-butyl peracetate, tert-butyl perbenzoate, 4,4-di-tert-butyl-peroxyvalerate n-butyl ester, 2,2-di-tert-butyl-peroxybutane, diisopropylbenzene peroxide, tert-butylisopropylbenzene peroxide, 1,3-bis(tert-butylperoxyisopropyl)benzene, di-tert-butyl peroxide and azoisobutyronitrile. Preferred free radical initiators are organic peroxides, particularly preferred are diisopropylbenzene peroxide.
[0096] Therefore, component (A3) comprises a compatibilizer or a mixture of a compatibilizer and a free radical initiator. The total amount of compatibilizing accelerator and free radical initiator is 0% to 4% by weight, preferably 0.1% to 4% by weight, and particularly preferably 0.2% to 3% by weight, based on the sum of (A1) to (A3). The free radical initiator is preferably 0% to 1% by weight, particularly preferably 0.05% to 0.8% by weight, based on the sum of (A1) to (A3).
[0097] In a preferred embodiment, the compatibilizer is graft polymerized without addition of a free radical initiator, ie component (A3) preferably comprises no free radical initiator.
[0098] Component (A4)
[0099] Besides polyamide (A1), polyphenylene ether (A2) and optionally compatibilizer (A3), the blend (A) according to the invention may contain 0% to 20% by weight of vinylaromatic and / or olefinic polymer (A4).
[0100] The olefin polymers are homo- or co-olefins, particularly preferably polymers based on ethylene, propylene and butene or copolymers thereof and copolymers with other α-olefin monomers, in particular 1-pentene, 1-hexene, 1-heptene, 1-octene and 1-decene.
[0101] The vinyl aromatic polymer is preferably polystyrene or a copolymer of styrene with other monomers having at least one olefinic double bond, such as α-olefins, ethylene, propylene and butene or acrylic acid or acrylates or butadiene. Particularly preferred are block copolymers having at least one block formed from vinyl aromatic monomers (block A) and at least one block formed from olefin monomers (block B), such as is present in styrene block copolymers.
[0102] The olefin and / or vinyl aromatic polymer used as component (A4) may be or contain natural rubber, polybutadiene, polyisoprene, polyisobutylene, copolymers of butadiene and / or isoprene with styrene or styrene derivatives and other comonomers, hydrogenated copolymers and / or copolymers formed by grafting or copolymerization with anhydrides, (meth)acrylic acid and its esters. Polymer (A4) may also be a grafted rubber having a crosslinked elastomeric core composed of butadiene, isoprene or alkyl acrylates and having a grafted shell of polystyrene, nonpolar or polar olefin homopolymers and copolymers (e.g. ethylene-propylene rubber, ethylene-propylene-diene rubber and ethylene-octene rubber or ethylene-vinyl acetate rubber), or nonpolar or polar olefin homopolymers and copolymers formed by grafting or copolymerization with anhydrides, (meth)acrylic acid and its esters. Polymer (A4) can also be a carboxylic acid functionalized copolymer, such as poly(ethylene-co-(meth)acrylic acid) or poly(ethylene-co-1-olefin-co-(meth)acrylic acid), wherein the 1-olefin is an olefin having more than 4 atoms or an unsaturated (meth)acrylate, including those copolymers in which the acid groups are partially neutralized by metal ions.
[0103] Component (A4) is advantageously selected from the group consisting of polystyrene, polybutadiene-polystyrene graft copolymers, styrene-ethylene-butylene-styrene block copolymers (SEBS), styrene-ethylene-propylene-styrene block copolymers (SEPS), styrene-butadiene-styrene block copolymers (SBS), styrene-styrene-butadiene-styrene block copolymers (SSBS), ethylene / propylene copolymers, ethylene / propylene / diene copolymers (EPDM), polyethylene (PE), polypropylene (PP), polybutadiene (PB), poly-4-methylpentene, ethylene-propylene copolymers, ethylene-butene copolymers, ethylene-methylhexadiene copolymers, propylene-methylhexadiene copolymers, ethylene-octene copolymers, ethylene-propylene-butene copolymers, ethylene-propylene-hexene copolymers, ethylene-propylene-methylhexadiene copolymers, poly(ethylene-vinyl acetate) (EVA), ethylene-ethyl acrylate copolymers (EEA), ethylene-hexene copolymers, ethylene-propylene-diene terpolymers and blends of these polymeric materials. Particularly preferably, these polymers (A4) are grafted with acrylic acid, methacrylic acid or maleic anhydride in a degree of grafting of 0.1% to 4.0% by weight, based on the grafted polymer (A4).
[0104] Further preferably, mixture (A) comprises as component (A4) at least one vinylaromatic polymer and optionally at least one polyolefin. Particularly preferably, mixture (A) comprises at least 5% by weight, particularly preferably at least 10% by weight, based in each case on the total amount of (A), of vinylaromatic polymer.
[0105] Preferably, the olefin and / or vinyl aromatic polymer (A4) is selected from the group consisting of styrene-ethylene-butylene-styrene block copolymers (SEBS), styrene-ethylene-propylene-styrene block copolymers (SEPS), styrene-butadiene-styrene block copolymers (SBS), styrene-styrene-butadiene-styrene block copolymers (SSBS), polyethylene (PE), polypropylene (PP), polybutadiene (PB), poly-4-methylpentene, ethylene-propylene copolymers, ethylene-butene copolymers, ethylene-methylhexadiene copolymers, propylene-methylhexadiene copolymers, ethylene-octene copolymers, ethylene-propylene-butene copolymers, ethylene-propylene-hexene copolymers, ethylene-propylene-methylhexadiene copolymers, poly(ethylene-vinyl acetate) (EVA), ethylene-ethyl acrylate copolymers (EEA), ethylene-hexene copolymers, ethylene-propylene-diene terpolymers and blends of these polymer materials.
[0106] Furthermore, the olefin and / or vinylaromatic polymer (A4) of the molding composition is preferably grafted with carboxylic acid or carboxylic anhydride groups, particularly preferably with acrylic acid, methacrylic acid or maleic anhydride, the degree of grafting preferably being 0.1% to 4.0% by weight, particularly preferably 0.4% to 2.5% by weight and especially preferably 0.5% to 2.0% by weight, in each case based on the grafted polymer (A4).
[0107] Component (B) is a glass-based filler, which is present in the polyamide molding composition in an amount of 10 to 40% by weight. The filler can be either fibrous or particulate, either alone or in a mixture. Thus, component (B) can contain a fibrous filler (reinforcer) or a particulate filler or a mixture of a reinforcing agent and a particulate filler. For the purposes of the present invention, the terms glass-based filler, glass filler or glass filler are used synonymously.
[0108] According to a preferred embodiment of the invention, the content of component (B) in the polyamide molding composition is preferably 15% to 35% by weight, particularly preferably 18% to 32% by weight, these amounts referring to the sum of components (A) to (E).
[0109] According to the invention, a glass filler (B) based on glass is used, the glass composition of which comprises at least 10% by weight of boron oxide and at most 15% by weight of magnesium oxide and calcium oxide in total, based on the composition of the glass.
[0110] According to a preferred embodiment of the present invention, the glass filler is based on a glass whose glass composition comprises 2 to 14 wt %, more preferably 4 to 12 wt %, for the sum of the magnesium oxide and calcium oxide contents, based on the glass composition.
[0111] According to another preferred embodiment of the present invention, the glass filler is based on a glass comprising 12 to 24 wt. %, more preferably 15 to 22 wt. %, of boron oxide, based on the glass composition.
[0112] The glass filler is preferably selected from the group consisting of fibers, ground fibers, particles, flakes, spheres, hollow spheres and mixtures thereof, preferably consisting of fibers, particles, flakes and mixtures thereof. More particularly preferably, the glass filler is glass fiber. Most particularly preferred as glass fiber is a glass fiber with a non-circular cross section and an axis ratio of the major cross-sectional axis to the minor cross-sectional axis of 2 to 6, preferably 3 to 5.
[0113] The glass filler can be surface treated. This can be done with a suitable sizing system or bonding promoter system. For this reason, systems such as based on fatty acids, waxes, silanes, titanates, polyamides, carbamates, polyurethanes, polyhydroxy ethers, epoxides, nickel or combinations or mixtures thereof can be used. Preferably, the glass filler is surface treated with aminosilanes, epoxysilanes, polyamides or mixtures thereof.
[0114] If fibers are selected as the glass filler of component (B), the glass fibers are preferably selected from the group consisting of chopped fibers, continuous fibers, and mixtures thereof, wherein the fibers have a circular or non-circular cross section. Non-circular or non-circular glass fibers are also referred to as flat glass fibers and may have an oval, elliptical, angular, rectangular, or nearly rectangular cross section.
[0115] The chopped glass fibers preferably have a fiber length of 1 mm to 25 mm, preferably 1.5 mm to 20 mm, more preferably 2 mm to 12 mm, most preferably 2 mm to 8 mm.
[0116] The chopped glass fibers preferably have a diameter of 5 μm to 20 μm, preferably 5 μm to 15 μm, particularly preferably 6 μm to 12 μm.
[0117] If glass fibers are used as continuous fibers (rovings), they preferably have a diameter of at most 20 μm, preferably at most 18 μm, particularly preferably from 5 μm to 17 μm.
[0118] In the case of flat glass fibers, the aspect ratio, i.e. the ratio of the major cross-sectional axis to the minor cross-sectional axis, is 2 to 8, preferably 2 to 6, particularly preferably 3 to 5. The length of the cross-sectional axis of the flat glass fibers is 3 μm to 40 μm. Preferably, the length of the minor cross-sectional axis is 3 μm to 20 μm, particularly preferably 4 μm to 10 μm, and the length of the major cross-sectional axis is 6 μm to 40 μm, particularly preferably 12 μm to 30 μm.
[0119] For the reinforcement of the polyamide moulding compounds according to the invention, it is also possible to use mixtures of fibres having a circular (round) and a non-circular (flat) cross section.
[0120] If glass spheres or glass particles are selected as the glass filler (B), their average volume diameter (D50) measured by laser diffraction according to ASTM B822-10 (2010) is preferably 0.3 μm to 100 μm, particularly preferably 5 μm to 80 μm, and particularly preferably 17 μm to 70 μm.
[0121] In addition, the glass filler has a relative permittivity of preferably at most 7, particularly preferably at most 5, and a dielectric loss factor of preferably at most 0.0040, particularly preferably at most 0.0030. According to IEC 61189-2-721 (2015), based on a 80 mm × 80 mm × 3 mm glass plate made of glass with glass filler, the relative permittivity and dielectric loss factor are measured using a split dielectric resonator (SPDR) of QWED, Poland, with a measuring frequency of 2.45 GHz and a measuring temperature of 23°C.
[0122] According to a preferred embodiment of the present invention, component (B) consists exclusively of a glass filler selected from the group consisting of glass fibers, milled glass fibers, glass particles, glass flakes, glass spheres, hollow glass spheres or combinations thereof, wherein the glass filler consists of glass, wherein the sum of the contents of magnesium oxide and calcium oxide is 2% to 14% by weight, and the content of boron oxide (BO) is 12% to 24% by weight, each based on the composition of the glass. Particularly preferably, the glass filler is completely formed by glass fibers.
[0123] In a particularly preferred embodiment, component (B) is selected as a glass filler, particularly preferably as a glass fiber, the glass of which comprises the following components: 52.0% to 57.0% by weight of silicon dioxide, 13.0% to 17.0% by weight of aluminum oxide, 15.0% to 22.0% by weight of boron oxide, 2.0% to 6.0% by weight of magnesium oxide, 2.0% to 6.0% by weight of calcium oxide, 1.0% to 4.0% by weight of titanium dioxide, 0% to 1.5% by weight of fluorine, and 0% to 0.6% by weight of basic oxides.
[0124] To improve the dielectric properties, component (C) is added to the molding composition according to the invention in a proportion of 20% to 50% by weight, preferably 25% to 45% by weight and particularly preferably 30% to 42% by weight, in each case based on the molding composition (AE total). Component (C) preferably has a high relative permittivity of at least 100 or at least 500 and preferably has a dielectric loss factor of at most 0.02 or at most 0.01, measured at a frequency of 2.45 GHz.
[0125] According to the present invention, metal titanates, metal stannates and metal zirconates and mixtures thereof are used as component (C). The above metal salts may be present alone or in the form of a mixture or in the form of a solid solution, preferably in the form of mixed crystals. Particularly preferred are metal titanates, the metal being selected from the group consisting of barium, strontium, calcium, magnesium, lead, zirconium, manganese, neodymium, bismuth, hafnium, tin, zinc and mixtures thereof. The above metals may be present in the titanate alone or in the form of a combination of two or three metals.
[0126] Specific examples of such metal salts are barium titanate, strontium titanate, calcium titanate, magnesium titanate, neodymium titanate, bismuth titanate, lead titanate, nickel titanate, zinc titanate, barium stannate, strontium stannate, calcium stannate, magnesium stannate, neodymium stannate, bismuth stannate, lead stannate, nickel stannate, zinc stannate, barium zirconate, strontium zirconate, calcium zirconate, magnesium, neodymium zirconate, bismuth zirconate, lead zirconate, nickel zirconate, zinc zirconate. Particularly preferred metal titanates may contain a portion of metal stannate and metal zirconate to improve dielectric properties.
[0127] Particularly preferred are combinations of two or three metal titanates, metal stannates and metal zirconates, preferably including at least one metal titanate. Particularly preferred are combinations of barium titanate and strontium titanate, combinations of barium titanate and neodymium titanate, combinations of barium titanate and strontium titanate and barium stannate, combinations of barium titanate and strontium titanate and magnesium zirconate, combinations of barium titanate and calcium titanate, and combinations of strontium titanate and magnesium titanate.
[0128] In particular, barium titanate, strontium titanate, strontium barium titanate and neodymium barium titanate are preferred as component (C). Regarding strontium barium titanate and neodymium barium titanate, it is particularly preferred if the molar fraction based on the barium metal titanate is in the range of 55% to 85%.
[0129] Component (C) is preferably used as a powder, wherein 90% by volume of the particles have a diameter less than 10 μm, preferably less than 5 μm, and 50% by volume of the particles have a diameter less than 5 μm, preferably 2.5 μm, as determined according to ISO 13320 (2009) using a Malvern Mastersizer 2000 instrument.
[0130] Preferably, the proportion of component (D) is from 2% to 6% by weight, preferably from 3% to 5% by weight, based in each case on the molding composition (total of A to E).
[0131] Component (D) is preferably an LDS (laser direct structuring) additive having a non-zero absorption coefficient for UV, VIS or IR radiation, which under the action of electromagnetic radiation, preferably as laser radiation, forms metal nuclei, which in the chemical metallization process promote and / or enable and / or improve the deposition of a metal layer to produce conductor tracks at the irradiation points on the molding surface, the LDS additive preferably having an absorption capacity in the visible and infrared radiation range, an absorption coefficient of at least 0.05, preferably at least 0.1, in particular at least 0.2, and / or preferably, an absorber is provided which transfers the radiation energy to the LDS additive.
[0132] Component (D) is preferably an LDS additive having a median particle size (D50) of 50 nm to 10 000 nm, preferably 200 nm to 5000 nm, particularly preferably 300 nm to 4000 nm, and / or an aspect ratio of at most 10, in particular at most 5. The D50 value given as a measure of the particle size is a measure of the median particle size, wherein 50% by volume of the sample are finer and another 50% of the sample are coarser than the D50 value (median) .
[0133] Preferably, component (D) is a LDS additive selected from the group of metal oxides, in particular so-called spinels having the general formula AB2O4, wherein A is a metal cation with a valence of 2 and B is a metal cation with a valence of 3. In this context, the metal cation A is preferably selected from the group consisting of magnesium, copper, cobalt, zinc, tin, iron, manganese and nickel, and combinations thereof, and the metal cation B is preferably selected from the group consisting of manganese, nickel, copper, cobalt, tin, titanium, iron, aluminum and chromium, and combinations thereof.
[0134] In particular, the LDS additive is preferably a copper-iron spinel, a copper-containing magnesium-aluminum oxide, a copper-chromium-manganese mixed oxide, a copper-manganese-iron mixed oxide, optionally each with oxygen vacancies, or copper salts and oxides, such as, in particular, copper(I) oxide, copper(II) oxide, basic copper phosphate, copper sulfate, and metal complexes, in particular chelate complexes of copper, tin, nickel, cobalt, silver and palladium or mixtures of these systems, and / or is in particular selected from the group consisting of copper-chromium-manganese mixed oxides, copper-manganese-iron mixed oxides, copper chromium oxides, copper tungstates, zinc iron oxides, cobalt chromium oxides, cobalt aluminum oxides, magnesium aluminum oxides and mixtures thereof and / or surface-treated / or oxygen-deficient forms. Possible systems are, for example, those described in WO-A-2000 / 35259 or Kunststoffe 92 (2002) 11, pages 2-7.
[0135] Also preferred as component (D) are LDS additives selected from the group of tin-based metal oxides, mixed metal oxides, metal hydroxides, metal sulfide oxides (based on tin). Particularly preferred are tin oxide and doped tin oxide, wherein the doping can be with antimony, bismuth, molybdenum, aluminum, titanium, silicon, iron, copper, silver, palladium and cobalt. In particular, tin oxide doped with antimony, titanium or copper is preferred. In addition, a mixture of tin oxide and at least one other metal oxide, in particular antimony oxide, is preferred as LDS additive. As other metal oxides, colorless high-refractive metal oxides are used, such as, in particular, titanium dioxide, antimony (III) oxide, zinc oxide, tin oxide and / or zirconium dioxide, and colored metal oxides, such as chromium oxide, nickel oxide, copper oxide, cobalt oxide, and especially iron oxide (Fe2O3, Fe3O4). In particular, a mixture of tin oxide and antimony (III) oxide is preferred.
[0136] Preferably, the doped tin oxide or metal oxide mixture or tin oxide is formed as a layer on a flaky substrate, in particular a phyllosilicate, such as synthetic or natural mica, talc, kaolin, glass flakes or silicon dioxide flakes. Mica or mica flakes are particularly preferred as substrates for the metal oxides. In addition, flaky metal oxides such as flaky iron oxide, aluminum oxide, titanium dioxide, silicon dioxide, LCP (liquid crystal polymer), holographic pigments or coated graphite flakes are also considered as substrates.
[0137] Particularly preferred are LDS additives based on mica, the surface of which is coated with metal-doped tin oxide. In particular, antimony-doped tin oxide is preferred. Examples of commercially available LDS additives according to the invention are: Lazerflair LS820, LS825, LS830 and Minatec 230A-IR from Merck, Stanostat CP40W, Stanostat CP15G or Stanostat CP5C from Keeling & Walker, Fabulase 322S, 330, 350 and 352 from Budenheim.
[0138] Particularly preferred LDS additives are copper chromite, copper tungstate, copper hydrogen phosphate and antimony-doped tin oxide, the latter preferably in combination with mica. Copper tungstate is very particularly preferred.
[0139] The polyamide molding composition according to the invention comprises, as component (E), 0 to 5% by weight of at least one additive which is different from components (A), (B), (C) and (D).
[0140] According to a preferred embodiment, the molding compositions of the invention comprise as component (E) 0.1 to 5% by weight, preferably 0.2 to 4% by weight, based on the sum of components (A) to (E), of at least one additive.
[0141] According to a preferred embodiment, the additives of component (E) are selected from the group consisting of stabilizers, antioxidants, antiozonants, processing stabilizers, processing aids, viscosity improvers, light stabilizers, UV stabilizers, UV absorbers, inorganic heat stabilizers, especially those based on copper halides and alkali halides, organic heat stabilizers, optical brighteners, crystallization promoters, crystallization retarders, flow aids, lubricants, slip agents, release agents, colorants, especially dyes, inorganic pigments, organic pigments, marking agents and mixtures thereof.
[0142] According to a particularly preferred embodiment, the molding composition of the invention comprises as component (E) at least one processing aid, which is preferably present in a proportion of 0% to 2% by weight, particularly preferably 0.1% to 2.0% by weight, and particularly preferably 0.1% to 1.5% by weight, most preferably 0.2% to 1.0% by weight, based in each case on the total weight of components (A) to (E). Preferred metal salts are aluminum (Al), alkali metals, alkaline earth metal salts, esters or amides of fatty acids containing 10 to 44 carbon atoms, preferably 14 to 44 carbon atoms, preferably the metal ions sodium (Na), magnesium (Mg), calcium (Ca) and Al, particularly preferably Ca or Mg. Particularly preferred metal salts are magnesium stearate, calcium stearate and calcium montmorillonate and aluminum stearate. The fatty acids may be monovalent or divalent. Examples are pelargonic acid, palmitic acid, lauric acid, margaric acid, dodecanedioic acid, behenic acid and particularly preferably stearic acid, capric acid and montanic acid (mixture of fatty acids having 30 to 40 carbon atoms).
[0143] According to a further preferred embodiment, the molding composition according to the invention comprises as component (E) at least one heat stabilizer, the proportion of which is preferably from 0% to 3% by weight, particularly preferably from 0.1% to 2.0% by weight, in each case based on the total weight of components (A) to (E).
[0144] According to a preferred embodiment, the heat stabilizer is selected from the group consisting of:
[0145] Compounds of monovalent or divalent copper, for example salts of monovalent or divalent copper with inorganic or organic acids or monovalent or divalent phenols, oxides of monovalent or divalent copper, or complexes of copper salts with ammonia, amines, amides, lactams, cyanides or phosphine, preferably copper(I) or Cu(II) salts of hydrohalic acids, copper(I) or Cu(II) salts of hydrocyanic acid or copper salts of aliphatic carboxylic acids. Particularly preferred are monovalent copper compounds CuCl, CuBr, CuI, CuCN and Cu2O, and divalent copper compounds CuCl2, CuSO4, CuO, copper(II) acetate or copper(II) stearate. Advantageously, the copper compound is used in combination with other metal halides, in particular alkaline halides (e.g. NaI, KI, NaBr, KBr), the molar ratio of metal halide to copper halide being 0.5 to 20, preferably 1 to 10 and particularly preferably 3 to 7;
[0146] Stabilizers based on aromatic secondary amines, the content of these stabilizers is preferably from 0.1% to 2% by weight, preferably from 0.2% to 0.5% by weight;
[0147] Stabilizers based on sterically hindered phenols, the content of these stabilizers is preferably from 0.1% to 1.5% by weight, preferably from 0.2% to 0.6% by weight;
[0148] Phosphites and phosphonites, and
[0149] Mixtures of the above stabilizers.
[0150] Examples of stabilizers based on aromatic secondary amines which can be used according to the invention are adducts of phenylenediamine with acetone (Naugard A), adducts of phenylenediamine with linol, Naugard 445, N,N'-dinaphthyl-p-phenylenediamine, N-phenyl-N'-cyclohexyl-p-phenylenediamine or mixtures thereof.
[0151] Suitable sterically hindered phenols are in principle all compounds with a phenol structure which have at least one sterically required group on the phenol ring. Preferred examples of stabilizers based on sterically hindered phenols which can be used according to the invention are N,N′-hexamethylene-bis-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionamide, bis-(3,3-bis-(4′-hydroxy-3′-tert-butylphenyl)-butyric acid) glycol ester, 2,1′-thioethyl-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionate, 4-4′-butylidene-bis-(3-methyl-6-tert-butylphenol), triethylene glycol-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)-propionate or mixtures of two or more of these stabilizers.
[0152] Preferred phosphites and phosphonites include triphenyl phosphite, diphenyl alkyl phosphites, phenyl dialkyl phosphites, tris(nonylphenyl) phosphite, trilauryl phosphite, trioctadecyl phosphite, distearyl pentaerythritol diphosphite, tris(2,4-di-tert-butylphenyl)phosphite, diisodecyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphite, diisodecyloxypentaerythritol diphosphite, bis(2,4-di-tert-butyl-6-methylphenyl) pentaerythritol diphosphite, bis(2,4,6-tri-(2,6-di-tert-butyl-4-methylphenyl) penta ...6-methylphenyl) pentaerythritol diphosphite, bis(2,4,6-tri-(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosph tert-butylphenyl) pentaerythritol diphosphite, tristearyl sorbitol triphosphite, tetrakis(2,4-di-tert-butylphenyl)-4,4'-bisphenylene diphosphonite, 6-isooctyloxy-2,4,8,10-tetra-tert-butyl-12H-dibenz-[d,g]-1,3,2-dioxaphosphite, 6-fluoro-2,4,8,10-tetra-tert-butyl-12-methyl-dibenzo[d,g]-1,3,2-dioxaphosphite ocine), 6-fluoro-2,4,8,10-tetra-tert-butyl-12-methyl-dibenz[d,g]-1,3,2-dioxaphosphocine, bis(2,4-di-tert-butyl-6-methylphenyl)methylphosphite and bis(2,4-di-tert-butyl-6-methylphenyl)ethylphosphite. In particular, tris[2-tert-butyl-4-thio(2'-methyl-4'-hydroxy-5'-tert-butyl)-phenyl-5-methyl]phenylphosphite and tris(2,4-di-tert-butylphenyl)phosphite (Irgafos 168) are preferred.
[0153] A preferred embodiment of the heat stabilizer is a combination of organic heat stabilizers, in particular a combination of Irgafos 168 and Irganox 1010 or a combination of HOSTANOX O 3P (bis[3,3-bis-(4'hydroxy-3'-tert-butyl-phenyl)butyric acid diol ester) and SANDOSTAB P-EPQ (tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenyl diphosphate). In particular, heat stabilization based only on CuI and KI is preferred.
[0154] Examples of oxidation retarders and heat stabilizers include phosphites and other amines (eg triacetonediamine), hydroquinone, variously substituted representatives of these groups and mixtures thereof in concentrations of up to 1% by weight, based on the weight of components (A) to (D).
[0155] Various substituted resorcinols, salicylates, benzotriazoles, benzotriazines and benzophenones are mentioned as UV stabilizers, which are generally used in amounts of up to 2% by weight, based on the weight of the molding composition.
[0156] Inorganic pigments, such as titanium dioxide, ultramarine blue, iron oxide and carbon black and / or graphite, and furthermore organic pigments, such as phthalocyanines, quinacridones, perylenes and dyes, such as nigrosine and anthraquinones, can be added as colorants. However, it is preferred that the molding composition according to the invention contains neither carbon black nor graphite, i.e. the molding composition according to the invention is preferably free of carbon black and graphite.
[0157] In a particularly preferred embodiment, the thermoplastic molding composition according to the invention consists of:
[0158] (A) a mixture of 24 to 57.9% by weight of at least one polyamide (A1), at least one polyphenylene ether (A2) and a compatibilizer (A3);
[0159] (B) 15 to 35 weight percent of glass fibers, the glass composition of the glass fibers comprising 12 to 24 weight percent of boron oxide and 2 to 14 weight percent of the sum of magnesium oxide and calcium oxide;
[0160] (C) 25 to 45 weight percent of a metal titanate selected from the group consisting of barium titanate, strontium titanate, barium strontium titanate, and barium neodymium titanate;
[0161] (D) 2 to 6 wt % of an LDS additive selected from the group consisting of copper chromium oxide, copper tungstate, copper oxide, copper hydroxide phosphate, hydrogen tin phosphate, tin phosphate, copper phosphate, basic copper phosphate and basic tin phosphate or mixtures thereof, preferably copper tungstate;
[0162] (E) 0.1 to 5 wt % of additives other than (A), (B), (C) and (D);
[0163] wherein the mixture (A) consists of 52 to 89.8% by weight of component (A2), 10 to 45% by weight of component (A1), 0.2 to 3% by weight of component (A3), in each case based on the sum of components (A1) to (A3), the sum of components (A1) to (A3) being 100% by weight of the mixture (A);
[0164] and wherein the sum of (B) and (C) is 40 wt % to 65 wt % based on the sum of (A) to (E);
[0165] And wherein the sum of components (A) to (E) is 100% by weight of the molding composition.
[0166] The molding compound according to the invention has good mechanical properties, can be easily metallized after irradiation, and is characterized by a relative permittivity of at least 5.0 and a low dielectric loss factor (DLF) of less than 0.008.
[0167] A preferred variant of the production of the molding compound according to the invention is that, in a first step, a mixture comprising components (A1) to (A4) is provided. To this end, components (A2), (A3) and optionally (A4) can first be metered into the feed section of the extruder and mixed in a temperature range of 220° C. to 340° C. The mixture is then added to a side feeder. Component (A) is then introduced via a side feeder into the molten mixture formed by components (A2) to (A4) in the housing of the extruder downstream of the feed. Alternatively, components (A1) to (A4) can also be metered into the feeder of the extruder and mixed in the extruder at a temperature of 220° C. to 340° C. In both variants, components (D) and / or (E) can be additionally included, wherein these components are preferably metered into the feed. Then, in a second extrusion step, mixture (A) and components (D) and (E) or a mixture of (A), (D) and (E) are metered into the feed of the extruder and melted at a temperature of 220° C. to 340° C., while components (B) and (C) are fed into the extruder housing downstream of the feed via a side feeder and mixed with the melt present.
[0168] Another preferred method for preparing the molding compound is to meter components (A1) to (A4), (D) and (E) into the feed of the extruder and melt and mix them at a temperature of 220° C. to 340° C. in the first extruder section, then feed components (B) and (C) into the melt via a side feeder and mix with the other components in the second extruder section. The molding compound is then discharged and, after cooling, pelletized. For high filler contents, underwater pelletization is preferred.
[0169] The present invention furthermore comprises a moulding which comprises or preferably consists of the above-described thermoplastic moulding composition according to the invention.
[0170] The molded body is preferably a component, a housing, or a housing component of a device that communicates via electromagnetic waves having a frequency of 0.3 GHz to 300 GHz.
[0171] In particular, the molded article is selected from the group consisting of transmitting and receiving devices, mobile phones, tablet computers, laptop computers, navigation devices, surveillance cameras, cameras, sensors, diving computers, audio systems, remote controls, loudspeakers, headphones, radios, televisions, household appliances, kitchen appliances, door openers or door openers, vehicle central locking operating devices, keyless start vehicle keys, temperature measuring or temperature display devices, components, housings or housing parts of measuring and control devices.
[0172] Example
[0173] Measurement method:
[0174] In the context of this application, the following measurement methods are used:
[0175] Relative viscosity
[0176] The relative viscosity (RV) is determined according to ISO 307 (2007) at 20° C. For this purpose, 0.5 g of polymer particles are weighed into 100 ml of m-cresol. The relative viscosity (RV) is calculated according to Chapter 11 of the standard as RV=t / t0.
[0177] Glass transition temperature (Tg) and melting point (Tm)
[0178] According to ISO 11357-2 and ISO 11357-3 (2013), the particles were subjected to the determination of glass transition temperature and melting point. Differential scanning calorimetry (DSC) was performed at a heating rate of 20K / min in each of the three heatings. After the first heating, the sample was cooled at a rate of 20K min, and the melting point was determined during the subsequent heating (second heating). The sample was then quenched in dry ice, and the glass transition temperature (Tg) was determined during the third heating. The temperature at the peak maximum is indicated as the melting point. The midpoint of the glass transition range was determined according to the "half-height" method, which shows the glass transition temperature (Tg).
[0179] Tensile modulus
[0180] The Young's tensile modulus was determined according to ISO 527 (2012) at 23°C and a tensile speed of 1 mm / min on ISO tensile bars (type A1, mass 170 x 20 / 10 x 4) prepared according to standard: ISO / CD 3167 (2003).
[0181] Breaking stress and breaking elongation
[0182] The tensile stress at break and the elongation at break were determined according to ISO 527 (2012) at 23°C at a tensile speed of 5 mm / min on the reinforcement on ISO tensile bars type A1 (mass 170 mm x 20 / 10 mm x 4 mm) prepared according to standard: ISO / CD 3167 (2003).
[0183] Relative permittivity and dielectric loss factor (DLF)
[0184] The relative permittivity εr and dielectric loss factor (DLF) were measured according to IEC 61189-2-721 (2015) on a 80 mm x 80 mm x 3 mm flat plate with a film gate using a Split Post Dielectric Resonator (SPDR) from QWED, Poland (a brochure including information related to the measurements can be obtained at www.qwed.eu). The measurement frequency was 2.45 GHz and the measurement temperature was 23°C.
[0185] Molding shrinkage
[0186] The plates (type D2, 60 mm x 60 mm x 2 mm, film gate) for the determination of splash shrinkage were prepared according to ISO 294-3 (2002) and amendment 1 (2006). According to ISO 294-4 (2001), after the plates were stored for 14 days in a standard climate (23°C, 50% relative humidity), the molding shrinkage in the longitudinal and transverse directions relative to the cavity dimensions and relative to the flow direction of the molding compound melt was determined. The arithmetic mean of the measurements on 5 plates is shown. The ratio of the injection molding shrinkage along and across the flow direction of the molding compound is also called warpage or deformation.
[0187] Laser Structuring and Metallization
[0188] To evaluate the metallization behavior, injection molded articles (flat plates 60 mm × 60 mm × 2 mm) were patterned using an Nd:YAG laser and then metallized in an electroless copper plating bath. During the laser structuring process, 16 adjacent 10 mm × 10 mm areas were irradiated on the surface of the injection molded articles. Laser structuring was performed using a FOBADP50 laser at a speed of 4 m / s at a wavelength of 1064 nm and an irradiation width of about 50 μm. Both the pulse frequency and the pulse width were adjusted. Both the pulse frequency and the current intensity of the laser were varied. For specific pulse frequencies of 5 kHz, 6 kHz, 7 kHz, and 8 kHz, the diode current of the laser was set to 24.0 amperes, 24.5 amperes, 25.0 amperes, and 25.5 amperes, respectively. After laser structuring, the molded articles were cleaned to remove residues from the laser process. The molded articles were subjected to an ultrasonic bath with a surfactant and deionized water in sequence. The cleaned moldings were then metallized in a reducing copper plating bath (MacDermid MID-Copper 100B1) for 20-30 minutes.
[0189] Metallization Evaluation
[0190] o: The average copper deposition thickness is at least 3 μm in less than 14 areas;
[0191] +: The average copper deposition thickness is at least 3 μm in 14 or 15 areas;
[0192] ++: the average copper deposition thickness is at least 3 μm in all 16 areas;
[0193] For the purposes of the present invention, sufficient metallization means that copper is deposited in at least 14 areas with an average thickness of at least 3 μm.
[0194] Glass composition of glass filler
[0195] The glass composition of glass fillers, in particular of glass fibers, was determined using the following determination methods: Inductively Coupled Plasma Optical Emission Spectroscopy (ICP OES) according to DIN 51086-2:2004, boron oxide content titrimetric determination according to ISO 21078-1:2008, X-ray fluorescence melt digestion method according to ISO 12677:2003, fluorine determination after high temperature hydrolysis according to DIN 51084:2008.
[0196] Preparation of polyamide molding compounds
[0197] For examples B1 to B3 according to the invention, the various compounds (A) were first prepared. For this purpose, the corresponding amounts of polyphenylene ether (A2) and compatibilizer (A3) were metered into the feed zone of a twin-screw extruder of the ZSK 25 type from Werner & Pfleiderer according to Table 2, and the polyamide component (A1) was introduced into the melt through 6 barrel zones of a side feeder in front of the discharge outlet. For the example of polyamide-1, the temperature of the first shell was set to 70° C., the temperature of the remaining shells was set to 260° C. to 290° C., and for the example of polyamide 2, the temperature of the remaining shells was set to 290° C. to 320° C. A speed of 300 rpm and a throughput of 10 kg / h were used, and atmospheric degassing was carried out. The strands were cooled in a water bath, cut and the resulting granules were dried under vacuum (30 mbar) at 100° C. for 24 h. The blend (A), the dry granules of polyamide or polyphenylene ether, were then mixed together with the additives (C), (D) and (E) to form a dry blend in the proportions shown in Table 2. The mixture was homogenized by a drum mixer for about 20 minutes. The molding compound was prepared on a twin-screw extruder of the type FED 26MTS of Feddem GmbH & Co. KG in the proportions shown in Table 2. The dry blend was metered into the feeder by a weighing feeder. The glass fiber (B) was metered into the side feeder by a weighing feeder, which conveyed the glass fiber (B) to the 6 housing units upstream of the mold into the melt. The temperature of the first housing was set to 80°C, the temperature of the remaining housings was set to 260°C to 280°C for Examples B2, B3 and VB2, and the temperature of the remaining housings was set to 280°C to 310°C for Examples B1 and VB2. A speed of 250 rpm and a throughput of 15 kg / h were used, and atmospheric degassing was performed. The lines were cooled by underwater granulation, cut and the resulting granules were dried under vacuum (30 mbar) at 110°C for 24h to a moisture content of less than 0.1% by weight.
[0198] Preparation of test samples
[0199] The test specimens were produced on an injection molding machine Modell Allrounder 420C 1000-250 from Arburg. For Examples B2, B3 and VB2, barrel temperatures from 260° C. to 280° C. and a mold temperature of 60° C. were used, and for Examples B1 and VB1, barrel temperatures from 290° C. to 320° C. and a mold temperature of 120° C. were used. Unless otherwise stated, the test specimens were used in the dry state; for this purpose, they were stored in a dry environment, i.e. on silica gel, at room temperature for at least 48 h after injection molding.
[0200] Table 1 Materials used in Examples and Comparative Examples
[0201]
[0202]
[0203] Table 2: Results
[0204]
[0205] 1) Deformation rate = ratio of transverse injection shrinkage to longitudinal injection shrinkage.
Claims
1. A thermoplastic molding composition, consisting of the following components: A mixture of at least one polyamide A1, at least one polyphenylene ether A2 and optionally a compatibilizer A3 and optionally an olefin and / or vinyl aromatic polymer A4; B 10 to 40 wt % of a glass filler, the glass filler having a glass composition comprising at least 10.0 wt % of boron oxide and at most 15 wt % of the sum of magnesium oxide and calcium oxide; C 20 to 50 wt% of a titanate, a stannate, a zirconate or a mixture thereof; D 1 wt % to 8 wt % of an LDS additive; E 0 to 5 wt% of additives other than component A, component B, component C and component D; wherein the mixture A consists of 80 to 100% by weight of a mixture M of components A1, A2 and A3 and 0 to 20% by weight of component A4, based in each case on the sum of components M and A4, and wherein the sum of component M and component A4 is 100% by weight of the mixture A; and wherein the mixture M consists, in each case based on the sum of the components A1 to A3, of 36% to 92% by weight of the component A2, 8% to 60% by weight of the component A1 and 0% to 4% by weight of the component A3, and wherein the sum of the components A1 to A3 is 100% by weight of the mixture M; and wherein, based on the sum of components A to E, the sum of component B and component C is in the range of 35 wt % to 70 wt %; And wherein the sum of components A to E is 100% by weight of the molding composition.
2. The thermoplastic molding composition according to claim 1, wherein The component A1 is present in the mixture M in a proportion of 10% by weight to 48% by weight, based on the sum of the components A1 to A3; and The component A2 is present in the mixture M in a proportion of 48% by weight to 89.9% by weight, based on the sum of the components A1 to A3; and The component A3 is present in the mixture M in a proportion of 0.1 wt % to 4 wt % based on the sum of the components A1 to A3; and / or The mixture A consists exclusively of the components A1 to A3.
3. Thermoplastic molding composition according to any one of the preceding claims, characterized in that The glass filler B is based on glass, and the composition of the glass includes: 2% to 14% by weight, based on the composition of the glass, of the sum of the contents of magnesium oxide and calcium oxide; and / or 12 to 24 wt % boron oxide, based on the composition of the glass; or 52.0 wt% to 57.0 wt% silica, 13.0 wt% to 17.0 wt% alumina, 15.0 wt% to 21.5 wt% boron oxide, 2.0 wt% to 6.0 wt% magnesium oxide, 2.0 wt% to 6.0 wt% calcium oxide, 1.0 wt% to 4.0 wt% titanium dioxide, 0 wt% to 1.5 wt% fluorine, 0 wt% to 0.6 wt% basic oxides.
4. The thermoplastic molding composition according to claim 3, characterized in that The glass filler B is selected from the group consisting of fibers, particles, flakes, balls or combinations thereof.
5. The thermoplastic molding composition according to claim 4, characterized in that The glass filler B is selected from glass fibers.
6. The thermoplastic molding composition according to claim 5, characterized in that The glass filler B is selected from glass fibers having a non-circular cross section and an axis ratio of a major cross-sectional axis to a minor cross-sectional axis in a range of 2 to 6.
7. The thermoplastic molding composition according to any one of claims 1 to 2, characterized in that The at least one polyamide A1 is selected as aliphatic polyamide from the group consisting of PA 46, PA 6, PA 66, PA 6 / 66, PA 10, PA11, PA 12, PA 516, PA 610, PA 612, PA 614, PA 616, PA 618, PA 1010, PA 1012, PA 1014, PA1016, PA 1018, PA 1212 and mixtures thereof; and / or A semicrystalline partially aromatic polyamide selected from the group consisting of PA 4T / 4I, PA 4T / 6I, PA 5T / 5I, PA 6T / 6, PA 6T / 6I, PA 6T / 6I / 6, PA 6T / 66, 6T / 610, 6T / 612, PA 6T / 10T, PA 6T / 10I, PA9T, PA 10T, PA 12T, PA 10T / 10I, PA10T / 106, PA10T / 610, PA10T / 612, PA10T / 66, PA10T / 6, PA10T / 1010, PA10T / 1012, PA10T / 12, PA10T / 11, PA 6T / 9T, PA 6T / 12T, PA 6T / 10T / 6I, PA6T / 6I / 6, PA 6T / 6I / 12 and mixtures thereof; and / or An amorphous polyamide or a microcrystalline polyamide selected from the group consisting of PA 6I / 6T, PA MACM9, PAMACM10, PA MACM12, PA MACM13, PA MACM14, PA MACM16, PA MACM17, PA MACM18, PA PACM10, PA PACM12, PA PACM13, PA PACM14, PA PACM16, PA PACM17, PA PACM18, PA TMDC10, PATMDC12, PA TMDC13, PA TMDC14, PA TMDC16, PA TMDC17, PA TMDC18, PA MACM10 / 10, PAMACMI / 12, PA MACMT / 12, PA 6I / MACMI / MACMT, PA MACMI / MACMT / MACM12, PA MACMI / MACMT / MACM12 / 12, PA 6I / 6T / MACMI / MACMT / 12, PA 6I / 6T / MACMI, PAMACMI / MACM36, PA MACMT / MACM36, PA MACMI / MACM12, PA MACMT / MACM12, PA MACM6 / 11, PAMACM10 / 10, PA MACM12 / PACM12, PA MACM14 / PACM14, PA MACM18 / PACM18 and their mixtures.
8. The thermoplastic molding composition according to any one of claims 1 to 2, characterized in that The polyphenylene ether of component A2 is selected from the group consisting of poly(2,6-dimethyl-1,4-phenylene) ether, poly(2,6-diethyl-1,4-phenylene) ether, poly(2-methyl-6-ethyl-1,4-phenylene) ether, poly(2-methyl-6-propyl-1,4-phenylene) ether, poly(2,6-dipropyl-1,4-phenylene) ether, poly(2-ethyl-6-propyl-1,4-phenylene) ether, or copolymers or mixtures thereof.
9. The thermoplastic molding composition according to any one of claims 1 to 2, characterized in that The component A3 is selected from a compatibilizer, which is selected from the group consisting of maleic acid, maleic anhydride, fumaric acid, acrylic acid, methacrylic acid, methylmaleic acid, methylmaleic anhydride, itaconic acid, itaconic anhydride, butenylsuccinic acid, butenylsuccinic anhydride, tetrahydrophthalic acid, tetrahydrophthalic anhydride, N-phenylmaleimide, citric acid, malic acid and 2-hydroxynonadecane-1,2,3-tricarboxylic acid, monoesters or diesters of the above acids with C1- to C12-alcohols, monoamides or diamides of the above acids, the monoamides or diamides optionally having an alkyl or aryl group with up to 12 carbon atoms on the nitrogen, salts with alkali metals or alkaline earth metals, and mixtures thereof; Or the component A3 is selected from a mixture of a compatibilizer and a free radical initiator; wherein the compatibilizer is selected from the group consisting of maleic acid, maleic anhydride, fumaric acid, acrylic acid, methacrylic acid, methyl maleic acid, methyl maleic anhydride, itaconic acid, itaconic anhydride, butenyl succinic acid, butenyl succinic anhydride, tetrahydrophthalic acid, tetrahydrophthalic anhydride, N-phenylmaleimide, citric acid, malic acid and 2-hydroxynonadecane-1,2,3-tricarboxylic acid, a monohydrate of the above acid and C1- to C12-alcohol Esters or diesters, monoamides or diamides of the above acids, the monoamides or diamides optionally having an alkyl or aryl group with up to 12 carbon atoms on the nitrogen, salts with alkali metals or alkaline earth metals, and mixtures thereof, and wherein the free radical initiator is selected from the group consisting of tert-butyl-peroxy-isopropyl-carbonate, tert-butyl-peroxy-3,3,5-trimethylhexanoate, tert-butyl peracetate, tert-butyl perbenzoate, diisopropyl peroxide, tert-butyl isopropyl peroxide, di-tert-butyl peroxide.
10. The thermoplastic molding composition according to claim 9, characterized in that The C1- to C12-alcohol is selected from methanol or ethanol; the alkaline earth metal is selected from calcium and potassium; the di-tert-butyl peroxide is selected from 1,1-di-tert-butyl-peroxy-3,3,5-trimethylcyclohexane, 4,4-di-tert-butyl-peroxyvalerate, 2,2-di-tert-butyl-peroxy-butane, and 1,3-bis(tert-butylperoxyisopropyl)benzene.
11. The thermoplastic molding composition according to any one of claims 1 to 2, characterized in that The olefin and / or vinyl aromatic polymer A4 is selected from the group consisting of styrene-ethylene-butylene-styrene block copolymers, styrene-ethylene-propylene-styrene block copolymers, styrene-butadiene-styrene block copolymers, styrene-styrene-butadiene-styrene block copolymers, polyethylene, polypropylene, polybutadiene, poly-4-methylpentene, ethylene-propylene copolymers, ethylene-butene copolymers, ethylene-methylhexadiene copolymers, propylene-methylhexadiene copolymers, ethylene-octene copolymers, ethylene-propylene-butene copolymers, ethylene-propylene-hexene copolymers, ethylene-propylene-methylhexadiene copolymers, poly(ethylene-vinyl acetate), ethylene-ethyl acrylate copolymers, ethylene-hexene copolymers, ethylene-propylene-diene terpolymers and mixtures of these polymer materials; and / or grafted with carboxylic acid or carboxylic anhydride groups; and / or grafted with acrylic acid, methacrylic acid or maleic anhydride, with a grafting degree of 0.1% to 4.0% by weight, based on the grafted polymer A4.
12. The thermoplastic molding composition according to any one of claims 1 to 2, characterized in that The component C is a metal titanate, the metal is selected from the group consisting of barium, strontium, calcium, magnesium, lead, zirconium, manganese, neodymium, bismuth, hafnium, tin and zinc, and the metal exists in the titanate alone or in combination.
13. The thermoplastic molding composition according to claim 12, characterized in that The component C is a metal titanate selected from the group consisting of barium titanate, strontium titanate, barium strontium titanate and barium neodymium titanate.
14. The thermoplastic molding composition according to any one of claims 1 to 2, characterized in that The component D comprises or is completely formed of at least one LDS additive based on copper and / or tin selected from the group consisting of metal oxides, metal phosphates, basic metal phosphates and / or metal hydroxide phosphates.
15. Thermoplastic molding composition according to claim 14, characterized in that The component C comprises or is completely formed of at least one LDS additive selected from the following group: tin oxide; metal or metal oxide doped tin oxide; mica coated with metal oxide; mica coated with antimony doped tin oxide; a mixture of tin oxide and antimony oxide and optionally other metal oxides; spinel; copper chromium oxide; copper tungstate, copper oxide; copper hydroxide; copper hydroxide phosphate; copper phosphate; basic copper phosphate; copper tin phosphate; basic copper tin phosphate; tin phosphate; basic tin phosphate; or mixtures and combinations thereof.
16. The thermoplastic molding composition according to claim 15, characterized in that The component C is selected from antimony-doped tin oxide.
17. The thermoplastic molding composition according to any one of claims 1 to 2, characterized in that The LDS additive of component D is selected from the group consisting of copper chromium oxide, copper tungstate, copper oxide, copper hydroxide phosphate, tin hydroxide phosphate, tin phosphate, copper phosphate, basic copper phosphate and tin phosphate, or a mixture thereof.
18. The thermoplastic molding composition according to any one of claims 1 to 2, characterized in that The additives of component E are selected from the group consisting of stabilizers, anti-aging agents, antioxidants, anti-ozonants, viscosity improvers, ultraviolet absorbers, optical brighteners, crystallization accelerators, crystallization retarders, flow aids, lubricants, mold release agents, dyes, inorganic pigments, organic pigments, marking agents, and mixtures thereof.
19. The thermoplastic molding composition according to any one of claims 1 to 2, characterized in that The additive of component E is selected from the group consisting of processing aids, colorants, and mixtures thereof.
20. The thermoplastic molding composition according to claim 18, characterized in that The additive of component E is selected from the group consisting of: processing stabilizer, light stabilizer, inorganic heat stabilizer, organic heat stabilizer, lubricating oil.
21. The thermoplastic molding composition according to claim 20, characterized in that The additives of component E are selected from the group consisting of UV stabilizers, inorganic heat stabilizers based on copper halides and alkaline halides.
22. The thermoplastic molding composition according to any one of claims 1 to 2, characterized in that Based on the sum of components A to E, component A is present in a proportion ranging from 24 wt % to 57.9 wt %; and / or based on the sum of components A to E, component B is present in a range of 15 wt % to 35 wt %; and / or based on the sum of components A to E, component C is present in a range of 25 wt % to 45 wt %; and / or based on the sum of components A to E, component B and component C are present in a range of 40 wt % to 65 wt %; and / or based on the sum of components A to E, component D is present in a range of 2 wt % to 6 wt %; And / or based on the sum of the components A to E, the component E is present in the range of 0.1 wt % to 5 wt %.
23. A moulding comprising or consisting of the thermoplastic moulding composition according to any one of claims 1 to 22.
24. The molded article according to claim 23, characterized in that The molded article is a component, a housing, or a housing part of a device that communicates with electromagnetic waves having a frequency of 0.3 GHz to 300 GHz.
25. The molded article according to claim 24, characterized in that The device is selected from the group consisting of: a mobile phone, a tablet, a laptop, a navigation device, a surveillance camera, a camera, a sensor, a diving computer, a remote control, a speaker, a headset, a radio, a television, a kitchen appliance, a door opening device, an operating device for a vehicle central locking system, a keyless start vehicle key, a temperature measuring device or a temperature indicating device.
26. The molded article according to claim 24, characterized in that The device is selected from the group consisting of: an audio system, a home appliance, a measuring device, and a control device.
27. The molded article according to claim 24, characterized in that The molded article is a component, a housing or a housing part of a transmitting and receiving device.
28. The molded article according to claim 25, characterized in that The device is a door opener.
